Play-write Poetry in Nicholson Baker’s The Anthologist - Yannicke Chupin (Transatlantica)
The following article focuses on the function of literary play in Nicholson Baker’s The Anthologist, a meta-fictional novel whose narrator Paul Chowder is a writer and poet who struggles to write the introduction of a forthcoming anthology of rhymed poetry. Whereas it is the competitive nature (agon) of literary creation that initially suspends the pleasure of creation, as will be reviewed in the first part of the analysis, it is through the virtues of educational play (paideia) and the creation of an alternative world that narrative creativity is released and produces the pages that constitute this book. Focusing on freedom as a pivotal concept in the creation of this contemporary Ars Poetica, the analysis then reviews the carnivalization of language and forms as a resourceful manifestation of literary play.